Ataxia Telangiectasia: A Case Report - Islam, MI; Hoque, SKA; Islam, MT; Saleh, ASM; Saha, NC; Rahman, AKM; Anwar, S; Banerjee, M (Journal of Dhaka Medical College, 2010)
Ataxia Telangiectasia (AT) is a rare, neurodegenerative disease that affects many parts of the body and causes severe disability is characterized by progressive Cerebellar ataxia, oculocutaneous telangiectasia, and recurrent respiratory and sinus infections. AT is caused by a defect in the ATM gene, which is responsible for recognizing and correcting errors in duplicating DNA when cells divide, and in destroying the cells when the errors can not be corrected. A 10 years old girl who is the first issue of non consanguineous parents completely immunized according to EPI schedule was admitted to Dhaka Medical College Hospital, Dhaka, on 26.01.2010 with the complaints of generalized weakness and difficulty to walk from the 6th year. The patient has one younger sister of 7 years old who has such complaints. On examination the patient was found mildly anemic with congestions in both eyeballs that is radiating from the both corners to limbus. The patient was conscious and cooperative. Cranial nerves were intact. There were hypotonia which was more marked in lower limbs with diminished jerks and flexor plantar reflexes. Gait was wide based and ataxic. She was diagnosed as a case of AT. This case is presented as academic interest. Key words: Ataxia Telangiectasia (AT); neurodegenerative disease. DOI: 10.3329/jdmc.v19i1.6258 J Dhaka Med Coll. 2010; 19(1) : 69-71.